KEMAMPUAN PREDATOR (Sycanus annulicornis Dhorn) DALAM MENGENDALIKAN HAMA ULAT API (Setothosea asigna) DI PERKEBUNAN KELAPA SAWIT - Wandi Marwadi Afandi; Sulthon Parinduri; Guntoro . (Jurnal Agro Estate, 2019)
Sycanus annulicornis is an important predator for palm leaf-eating caterpillars (UPDKS) from the Limacodidae family. Therefore, these predators need to be propagated and disseminated in the area of ​​oil palm plantations so that they can become a mortality factor in biological control (UPDKS). Predator S. annulicornis is a predator that is very useful for controlling caterpillar pests in oil palm plantations. His ability to prey on fire caterpillars in the field, as well as his short life cycle and high reproductive ability make this predator very potential to be applied in fire caterpillar pest control. This research was carried out at Sycanus House Afdeling V Tanah Raja PT. Perkebunan Nusantara III Serdang Bedagai North Sumatra. The time of the study was carried out in August - September 2018. The results showed that fire caterpillar (Setothosea asigna) was able to be controlled by predators (Sycanus annulicornis) in F1 treatment (1 Sycanus annulicornis), F2 (2 Sycanus annulicornis) and F3 on the first day after application, the highest mortality seen in the treatment F3 (3 Sycanus annulicornis).